Translocation of Precision Polymers through Biological Nanopores. Issue 24 (16th November 2017) - Boukhet, Mordjane; König, Niklas Felix; Ouahabi, Abdelaziz Al; Baaken, Gerhard; Lutz, Jean‐François; Behrends, Jan C.
Abstract: Nanopore analysis, which is, currently, chiefly used for DNA sequencing, is also an appealing technique for characterizing abiotic polymers. As a first step toward this goal, nanopore detection of non‐natural monodispersed poly(phosphodiester)s as candidate backbone structures is reported herein. Two model homopolymers containing phosphopropyl repeat units (i.e., 56 or 104 r.u.) and a short thymidine nucleotide sequence are analyzed in the present work. They are tested in two different biological nanopores, α‐hemolysin from Staphylococcus aureus, and aerolysin from Aeromonas hydrophila . These recordings are performed in aqueous medium at different KCl concentrations and various driving voltages. The data show a complex interaction with evidence for voltage dependence and threading, and underline the influence of the molecular structure and orientation of the precision poly(phosphodiester)s on the observed residual current signal as well as on the translocation dynamics. In particular, they suggest a dominant entropic contribution due to the high flexibility of the phosphodiester homopolymer. Abstract : Nanopore‐based electrical detection of poly(phopsphodiester)‐based homopolymers is shown using biological pore‐forming membrane proteins. This is a first important step toward a fast electrical readout system for information encoded in sequence‐controlled synthetic polymers. Importantly, these first results highlight the strong influence of polymer conformation on voltage‐dependent threading through the pore.